Integrated Digital Marketing Communications and Customers’ Revisit Intentions toward Michelin-Starred Restaurants in Thailand - Limpasuvanna, Savica; Supich, Apinya (ARU Research Journal Humanities and Social Sciences, 2026)
The objectives of this research were: 1) to study the levels of integrated marketing communications through digital media and the intentions to revisit Michelin-starred restaurant customers in Thailand; and 2) to analyze the influence of integrated marketing communications on intentions to revisit Michelin-starred restaurant customers in Thailand. The sample size was determined using a formula for an unknown population at a 95% confidence level and a 5% margin of error.Data were collected from 400 customers visiting Michelin-starred restaurants more than once, using a multi-stage sampling method. The research instrument was a three-part questionnaire covering: 1) personal characteristics, 2) perceptions of integrated marketing communications through digital media, and 3) intentions to revisit Michelin-starred restaurants. Data analysis was conducted using frequency, percentage, mean, standard deviation and Multiple Regression Analysis. The findings revealed that: 1) The overall level of integrated marketing communications through digital media as perceived by Michelin-starred restaurant customers was at a high level ( = 4.08, S.D. = 0.60) and the overall level of intentions to revisit of Michelin-starred restaurant customers was also at a high level ( = 4.14, S.D. = 0.58); and 2) Integrated marketing communications through digital media had a significant influence on the revisit intentions of Michelin-starred restaurant customers in Thailand, collectively accounting for 82.00% of the variance (R² = 0.820).